World politics - Haynes, Jeffrey, 1953-; Hough, Peter, 1967-; Malik, Shahin, ....- (Edinburgh Gate : Pearson Education Limited, 2011)
From the war on terror to the global financial crisis, traditional concepts of world politics are being challenged on a daily basis. In these uncertain times, the study of international relations and the forces that shape them have never been more important. Written specifically for students who are approaching this subject for the first time, World Politics is the most accessible, coherent and up-to-date account of the field available. It covers the historical backdrop to today's political situations, the complex interactions of states and non-state actors, the role of political economy, human security in all its forms, and the ways in which culture, religion and identity influence events.
Bibliography: p. [717]-738. - Includes index.
Keywords: Globalization; Go international; International office; International relations -- History -- 21st century; Wereldpolitiek; World politics -- 21st century